Evolution and trends in online dance instruction: a comprehensive literature analysis - Li, Jiaolu; Ahmad, Mohamad Aznillah (Frontiers in Education, 2025)
Literature related to the topic of “online dance” was selected as a sample through the database Web of Science (WoS), and the number of publications, the distribution of research countries and regions, and the distribution of research institutions were analyzed. Through analyzing the keywords, we analyze the research hotspots of online dance teaching from three perspectives: the educational environment and learning scenarios, the transformation of teaching methods and approaches, and the research objects and their impacting factors, sort out their paths of evolution, and carry out cutting-edge analyses. Two implications of the study were drawn: a focus on the use and continuation of new technologies in the development of dance teaching and learning, and a flexible and open-minded approach to the design of online dance courses.